IDEATIONAL AND INTERPERSONAL MEANINGS OF CHILDREN NARRATIVES IN INDONESIAN PICTUREBOOKS - Hermawan, Budi; Sukyadi, Didi (Universitas Pendidikan Indonesia, 2017)
Recent understanding as strongly believed by studies investigating the interactive or interpersonal meanings of images in such printed texts as textbooks and picturebooks shows that interpersonal relation can be established not only through verbal sentences as the primarily representational mode of our experiences but can also be represented through visual forms such as photographs and pictures. Further, studies on how meanings are represented through verbal and visual modes have revealed how readers’ experiences and readers’ social roles in relation to the content of the texts are constructed. The construction of readers’ social roles through the use of images in printed texts has been regarded to be parallel with how interactants’ social position is enacted in direct communication relying on the use of verbal sentences. In Indonesian contexts, however, studies on how verbal and visual modes represent experiences and construct social position of the interactants seem to be underexplored. The present study examined three Indonesian picturebooks using the perspectives of multimodality and reported how the children’s experiences were represented through the verbal and the visual modes used, and how these two semiotic resources represented the social relationship between the characters in the picturebook and the potential readers of the books. The examination of the verbal texts has been focused on the clauses as the building blocks of the texts by identifying the participants, process types, circumstances, and clause types. The examination of the pictures has been focused on such visual elements as who/what are in the picture, what activities taking place, the attributes possessed by the represented participants, and the circumstances. In addition, how the represented participants address the viewers was also examined. The results of the analysis show that ideationally the narrative is mostly centered around the activities done by and to children, which are presented as an offer to the readers. Verbally and visually the represented participants are socially equal to the children readers. The three picturebooks are excellent examples of picturebooks that present a narrative of Indonesian children designed for young readers because of their simple vocabulary, simply-constructed Indonesian grammar employed, and simple yet interesting plot they deal with.